MOLECULAR DOCKING OF BREAST CANCER RECEPTORS AGAINST ANTI-CANCER DRUG SOLASODINE (Applied Biological Research, 2024)
Cancer is a deadly disease that occurs in skin, pancreas, breast, and other body  parts. Breast cancer is nowadays more common and can develop from various  cell lines like MCF-7, MDA-MB-231, BT-20, etc. Early diagnosis and treatment  can reduce the frequency of fatalities due to breast cancer, but early cancer  screenings are often postponed due to erroneous information, fear, and  ignorance. In the present work, we used molecular docking to find out the  effect of solasodine binding on different cancer receptors. Solasodine was  extracted from black nightshade (Solanum nigrum), a weed that was long used  against stomach ache in Ayurveda. The isolated solasodine was even used in  ointments against skin cancer. Docking such a medicinally potent compound  resulted in positive response against a few receptors like Farnesoid X,  epidermal growth factor receptor and progesterone receptor. MCF-7 breast  cancer cell line was chosen for further ex-vivo studies and the results of MTT  assay showed significant anti-cancer effects at solasodine concentrations of 500  and 1000 µg mL-1. These findings indicated that Solasodine was a vital  candidate as drug against breast cancer.
Keywords: Autodock; breast cancer; discovery studio; Farnesoid x receptor; molecular docking; solasodine